Processes and time scales of magmatic evolution as revealed by Fe–Mg chemical and isotopic zoning in natural olivines. (1st April 2015) - Oeser, Martin; Dohmen, Ralf; Horn, Ingo; Schuth, Stephan; Weyer, Stefan
Abstract: In this study, we applied high-precision in situ Fe and Mg isotope analyses by femtosecond laser ablation (fs-LA) MC-ICP-MS on chemically zoned olivine xeno- and phenocrysts from intra-plate volcanic regions in order to investigate the magnitude of Fe and Mg isotope fractionation and its suitability to gain information on magma evolution. Our results show that chemical zoning (i.e., Mg#) in magmatic olivines is commonly associated with significant zoning in δ 56 Fe and δ 26 Mg (up to 1.7‰ and 0.7‰, respectively). We explored different cases of kinetic fractionation of Fe and Mg isotopes by modeling diffusion in the melt or olivine and simultaneous growth or dissolution. Combining the information of chemical and isotopic zoning in olivine allows to distinguish between various processes that may occur during magma evolution, namely diffusive Fe–Mg exchange between olivine and melt, rapid crystal growth, and Fe–Mg inter-diffusion simultaneous to crystal dissolution or growth. Chemical diffusion in olivine appears to be the dominant process that drives isotope fractionation in magmatic olivine. Simplified modeling of Fe and Mg diffusion is suitable to reproduce both the chemical and the isotopic zoning in most of the investigated olivines and, additionally, provides time information about magmatic processes. For the Massif Central (France), modeling of diffusive re-equilibration of mantle olivines in basanites revealed a short time span (<2 years) between the entrainment of a mantle xenolith in an intra-plate basaltic magma and the eruption of the magma. Furthermore, we determined high cooling rates (on the order of a few tens to hundreds of °C per year) for basanite samples from a single large outcrop in the Massif Central, which probably reflects the cooling of a massive lava flow after eruption. Results from the modeling of Fe and Mg isotope fractionation in olivine point to a systematic difference between β Fe and β Mg (i.e., β Fe / β Mg  ≈ 2), implying that the diffusivity ratio of 54 Fe and 56 Fe (i.e., D 54Fe / D 56Fe ) is very similar to that of 24 Mg and 26 Mg, despite the smaller relative mass difference for the 54 Fe– 56 Fe pair. This study demonstrates that a combined investigation of Fe–Mg chemical and isotopic zoning in olivine provides additional and more reliable information on magma evolution than chemical zoning alone.